2005
DOI: 10.1002/ajh.20273
|View full text |Cite
|
Sign up to set email alerts
|

Acute leukemia associated with valproic acid treatment: A novel mechanism for leukemogenesis?

Abstract: Valproic acid has been previously associated with hematologic toxicity, including a reversible myelodysplasia-like syndrome without chromosomal abnormalities. We now report three cases of acute leukemia with features of secondary leukemia associated with valproic acid therapy: two cases of acute myelogenous leukemia with multilineage dysplasia, one with trisomy 8 and one with monosomy 7, and one case of secondary acute lymphoblastic leukemia with del (7) (q22q34), del (9) (q21.11q22), del (11) (q12q23). One pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…However, the demethylation activity of valproate has not been confirmed by other groups. It has been reported that patients treated with valproate may develop overt acute leukemia (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the demethylation activity of valproate has not been confirmed by other groups. It has been reported that patients treated with valproate may develop overt acute leukemia (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence indicates that valproic acid may contribute to genomic instability, because a growing body of evidence demonstrates that valproic acid alters chromatin structure because it can function as a histone deacetylase inhibitor, leading to the acetylation of histone tails (Marchion et al, 2005). This change in the chromatin structure relaxes the conformation of DNA, making it more susceptible to DNA damage, including double-strand breaks (Coyle et al, 2005). Valproic acid's histone deacetylase activity has been attributed to certain pathologies, including valproic acidinduced teratogenesis and valproic acid-associated acute leu- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 molpharm.aspetjournals.org kemia, and is the basis behind the current testing of the effectiveness of valproic acid in cancer therapy (Phiel et al, 2001;Camphausen et al, 2005;Coyle et al, 2005).…”
Section: Valproic Acid-induced Homologous Recombination 1307mentioning
confidence: 99%
“…The reason is because it can function as a HDAC inhibitor, leading to the acetylation of histone tails (Marchion et al, 2005) and the relaxing of chromatin, thus making it more susceptible to DNA damage, including DSBs (Coyle et al, 2005). It has been shown that phosphorylated histone H2A.X (γH2A.X) is an early marker of DNA DSBs that can lead to altered gene expression and induction of apoptosis (Coyle et al, 2005;Marchion et al, 2005). HDAC activities should be effectively blocked by VPA as revealed by histone H3 acetylation.…”
Section: Discussionmentioning
confidence: 99%